Assessment of Obesity-related Metabolic Conditions: a novel objective scoring system better informs metabolic disease severity - Lyo, Victoria; Arriola, John; Ahmed, Shushmita M.; Mostaedi, Rouzbeh; Akinjobi, Zainab; Shamseddeen, Hazem N.; Ali, Mohamed R. (Surgery for obesity and related diseases, 2025)
Reporting of obesity-associated metabolic disease severity and longitudinal response to bariatric surgery is not standardized. We updated our co-morbidity scoring tool to the Assessment of Obesity-related Metabolic Conditions (AOMC) to combine pharmacotherapy and biochemical data to score diabetes mellitus (DM), hypertension (HTN), and dyslipidemia (DYS) severity. The aim of this study is to determine whether the AOMC system more accurately stages metabolic disease severity than a clinically based Assessment of Obesity-Related Comorbidities (AORC) system. University hospital, United States. A retrospective cohort study of prospectively collected demographic, clinical, and biochemical data was performed on adults evaluated for bariatric surgery over 6years. AORC versus AOMC scores and disease severity were compared using McNemar’s and Wilcoxon’s tests. Of 1442 patients, AOMC newly diagnosed metabolic disease in more patients than did AORC: DM (73.4% versus 44.5%), HTN (91.7% versus 67.9%), and DYS (63.8% versus 53.4%). Of those on pharmacotherapy, AOMC found fewer patients with adequately controlled disease: DM (39.9% versus 97.7%), HTN (64.7% versus 99.3%), and DYS (51.8% versus 99.0%). For those in whom both scores could be calculated, disease severity was upstaged in most patients: DM (65.9%), HTN (42.9%), and DYS (30.9%). There were also significant shifts toward higher scores for all conditions and severity classifications, with more patients diagnosed with pre–metabolic and severe disease (untreated/uncontrolled). Our study demonstrated that the severity of DM, HTN, and DYS is vastly under-represented by clinical history alone and lacks standardized assessments. Our AOMC tool more accurately describes longitudinal metabolic response to bariatric surgery. •Assessment of Obesity-related Metabolic Conditions (AOMC) is a new 6-point scoring system that objectively describes metabolic disease severity based on pharmacotherapy and biochemical data.•AOMC identified more diabetes, hypertension, and dyslipidemia than by a clinical scoring system.•AOMC identified more patients with inadequately controlled disease and overall higher disease severities.•The AOMC tool may be used to describe longitudinal metabolic response to bariatric surgery more accurately.